SHRINKING FOREST AND CONTESTED FRONTIERS: A CASE OF CHANGING HUMAN-FOREST INTERFACE ALONG THE PROTECTED AREAS OF NAGAON DISTRICT, ASSAM, INDIA - SINGHA, Kuleswar; SAHARIAH, Dhrubajyoti; SAIKIA, Anup (European Journal of Geography, 2019)
Anthropogenic activities have resulted in manifold land use/land cover (LULC) changes across the globe particularly since the 1980s. In this study, LULC changes of Nagaon district, India were assessed from 1987 to 2013 by using Landsat TM, Landsat ETM+ and Landsat 8 OLI/TIRS images. The study demonstrates the consistent increase of non-forest areas within and outside reserved forests (RF) and in mining areas. Dense, open / degraded forest and trees outside RFs consistently declined during the entire period. Dense forest decreased by 8173.1 ha (13.5%) during 1987-2001, and 4340.5 ha (10.2 %) during 2001-13. Similarly, open /degraded forest registered losses of 1449.5 ha (2.4%) during 1987-2001 and 429.7 ha (1%) during 2001-13. Trees outside forest areas also experienced losses of 16897.7 ha (27.9%) and 12803.1 ha (30%) during 1987-2001 to and 2001-13 respectively. The overall supervised classification accuracies were 91.1%, 89.1% and 90 % and Kappa values were 0.89, 0.87, and 0.88 during1987, 2001, and 2013, respectively.